FEAR AND MORAL PANIC IN POSTMODERN SOCIETY - Nedeljković, Zoran; Semenov, Andrej (Political Review, 2025)
In this paper, the author, based on relevant literature, approached the interpretation of the concepts of fear and moral panic using comparative-historical and hermeneutic methods. Fear is analyzed as a feeling, but also as a means of mass manipulation by the ruling elites. Individual fear is presented as the cause of moral panic, which, on the other hand, as a collective fear, intensifies the promotion of fear in the “free” citizen in postmodern societies. Through mass media, information and telecommunication networks, an individual cannot so imperceptibly escape the fate of a stigmatized person, the scapegoat for the existing crisis in society. In the armed conflicts that are intensifying in the twenty-first century, humane values seem to be marginalized like a footnote in a text, difficult for public opinion to read. The fear of death as a primal fear, the fear of all fears, has turned into a fear of the warring man, transformed into moral panic, and finally, which is devastating for the human species, into a fear of man himself.